Coupled simulations with SOLPS-ITER and B2.5-Eunomia for detachment experiments in Magnum-PSI. (1st April 2023) - Gonzalez, J; Chandra, R; de Blank, H J; Westerhof, E
Abstract: Heat loads of 10 MW m −2 are expected for steady state operation at ITER and up to 20 MW m −2 in slow transient situations. Plasma linear devices like Magnum-PSI can recreate situations close as those expected to be achieved at ITER divertor, providing easier access for diagnostics than in a tokamak. Numerical models are still necessary to complement experiments and to extrapolate relevant information to fusion devices, as the relevant atomic and molecular processes. SOLPS-ITER (formerly known as B2.5-Eirene) is typically employed to solve the plasma and neutral distribution in a coupled way for tokamak devices. For Magnum-PSI, B2.5 has been coupled with a different neutral module, named Eunomia, developed mostly for linear devices. Nevertheless, there is an interest in using SOLPS-ITER for simulating Magnum-PSI, as it would ease the process of relating linear device results with tokamaks. A previous work found significant differences in the implementation of relevant plasma-neutral processes in Eirene and Eunomia. A wide range of plasma scenarios are compared between B2.5-Eunomia and SOLPS-ITER. Although both codes produce results close to experimental Thomson scattering density and temperature near the target once the electric potential at the source is adjusted, these are achieved with completely different plasma and neutral distributions. Anomalous transport coefficients, which are other of the free-parameters in Magnum-PSI simulation, are set equal between the two codes. When studied in a wide range of neutral pressures, SOLPS-ITER shows a trend closer to experiments, as well as providing a converged solution at neutral pressures higher than 4 Pa for which B2.5-Eunomia was unable to provide a converged solution. Additional measurements of the neutral distribution in the target chamber as well as the electric potential at the source are required to determine which code is producing results closer to the experiment.